The relationship between lateral femoral condyle ratio measured by MRI and anterior cruciate ligament injury - Sun, Yang; Tang, Yun (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Previous studies have shown that the lateral femoral condyle ratio (LFCR)measured by X-ray has a significant relationship with the anterior cruciate ligament(ACL) injury. However, few relevant studies have been performed on LFCR measured by magnetic resonance imaging (MRI).: (1) To evaluate the relationship between LFCR measured by MRI and ACL injury or rerupture. (2) To compare the LFCR measured by MRI with existing bony morphological risk factors and screen out the most predictive risk factors for primary ACL injury or rerupture. Study Design：Cohort study; Level of evidence, 3. Methods: Totally 147 patients who underwent knee arthroscopic surgery from 2015 to 2019 with minimum follow-up of 48 month were retrospectively evaluated. Patients were placed into three groups: the control group of patients with simple meniscus tears without ligament injury;the primary noncontact ACL injury group;ACL rerupture group (ACL reconstruction failure). The LFCR measured by MRI and other previous known risk factors associated with MRI (notch width index, medial tibial slope, lateral tibial slope, medial tibial depth, lateral tibial height) were performed to evaluate their predictive value for ACL injury and rerupture. All the risk factors with P < 0.01 according to univariate analysis were included in the logistic regression models. Receiver operating characteristic (ROC) curves were analyzed for sensitivity, specificity, cut-off, and area under the curve (AUC). Z tests were used to compare the AUC values.The LFCR measured by MRI was obviously higher in primary ACL injury group (0.628±0.020) and in ACL rerupture group (0.625±0.021) than that in the control group(0.593±0.030). The best risk factor was the LFCR with a cut-off of 0.602 (AUC, 0.818; 95% CI, 0.748-0.878; sensitivity, 90%; specificity, 66%). When combined with lateral tibial slope (cutoff, 7°) and lateral tibial height (cutoff,3.6 mm), the diagnostic performance was improved significantly (AUC,0.896; 95% CI,0.890-0.950; sensitivity,87%; specificity,80%).The increased LFCR measured by MRI was associated with a significantly higher risk for ACL injury or rerupture. The combination of LFCR, lateral tibial slope and lateral tibial height were the most predictive risk factors. This may help clinicians identify susceptible individuals and allow precision approaches for better prevention, treatment and management of this disease.